Ultrasonic waves: Bioeffects on yeast cells - Domingos, R. N. [UNESP]; Angelis, D. F. de; Domingos, R. N.; Corso, C. R.; Menegario, A. A. [UNESP]; MendezVilas, A. (World Scientific Publ Co Pte Ltd, 2012)
Applications of ultrasound were starting from 1912 with the primary objective the detection of icebergs on prevention of maritime accidents. Algae, fish deaths and destruction were observed in the vicinity of sonar that equipped ships and submarines during the First World War.The evolutions of research and studies with ultrasound have big advances following the discovery of piezoelectric transducers in science and technology. As an example we can mention its application in microsurgery, fatigue detection in aerospace mechanics, catalysis sonochemical, biotechnology and others.The work presented here aims to demonstrate the application of ultrasonic in pulsed mode beams in biotechnology with the aim of improving the fermentation of a culture broth containing biological agents. In these experiments we used as ultrasound equipment and oscilator Sonics VCX-600 (20KHz), probe type wave guide. The experiments were conducted in a glass reactor of 200 mL of biomaterial containing cane juice and Saccharomyces cerevisiae in suspension. The parameters analyzed were related to the content Alcohlic (FID gas chromatography), and cell viability (Neubauer chamber), TRS (refractometry). Analysis of results showed that the total production exceeded in irradiated samples compared to normal fermentation (without ultrasound), suggesting additional advantage of ultrasound activation. Lastin Trials 1400 min, showed ethanol production systems 12% more than non-enabled systems. In this context alternatives for ethanol production, bio fuel and many other byproducts of the alcohol industries and chemicals could benefit from the use of ultrasound beams in this range of frequencies.
Keywords: Ultrasound; Saccharomyces cerevisiae; sonochemical catalysis; fermentation; ethanol